The worth and values of education - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Singapore’s education minister Heng Swee Keat surprised parents and educators when he indicated last September at his first major policy address a desire for education in Singapore – which has come under criticisms for its emphasis on grades- to return to the basics of moulding students’ characters.